Efektivitas Media Audio Visual dalam Pembelajaran Bulutangkis : Systematic Literature Review - Telaumbanua, Rolius; Hidayat, Yusuf; Rahmat, Alit (MAN Insan Cendekia Jambi, 2025)
This study presents a literature review using the Systematic Literature Review (SLR) method, employing the Preferred Reporting Item for Systematic Reviews and Meta-Analysis (PRISMA) guidelines. Google Analyst, ScienceDirect, and the National Library of Medication were utilized as the primary information sources, with the SLR process serving as the research instrument. Out of 583 identified articles, only 8 were selected as the main sources. The results of the analysis indicate that the utilization of visual media, particularly through video and sound visuals, has a significant positive impact on improving the basic skills of badminton students at the elementary, junior high, and college levels. The enhancement of understanding in techniques such as forehand service, pulverizing badminton, and executing a brief advantage strike occurs through the integration of visual media, serving not only as a supplementary tool but also as an active medium. Success is determined by the variety of teaching methods and the level of media interactivity, providing students with opportunities for active participation. In conclusion, the judicious use of visual media in badminton education can create a comprehensive learning experience, motivate students, and drive the achievement of excellence in badminton skills across various educational levels.